2010
DOI: 10.1038/modpathol.2009.191
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet-associated PAT-proteins show frequent and differential expression in neoplastic steatogenesis

Abstract: In many human cancers, lipogenic pathways are activated; in some tumors, such as hepatocellular carcinoma, this is reflected by the presence of visible lipid droplets. Yet, the biology of steatogenesis in malignant tumors is largely unknown. We have recently shown that lipid droplet-associated proteins of the PAT-family, named after their constituents perilipin (perilipin 1), adipophilin (perilipin 2), and TIP47 (perilipin 3) are differentially expressed in hepatic steatogenesis. We have comprehensively invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 34 publications
8
99
0
Order By: Relevance
“…Although ADRP and TIP47 typically target adipocytes, limited studies suggest that they also play a critical role in the formation and turnover of ectopic lipid droplets outside adipose tissue 34. For example, intracytoplasmic lipid droplets have been identified in a variety of cancers with expression of ADRP and TIP47 noted in cancer cells 10. The current study expands the role of these lipid droplet associated proteins to non-adipocyte stromal cells in the pancreas and suggests that these cells may have a crucial role in supporting the metabolism of cancer cells by protecting a renewable source for energy to stimulate tumour progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ADRP and TIP47 typically target adipocytes, limited studies suggest that they also play a critical role in the formation and turnover of ectopic lipid droplets outside adipose tissue 34. For example, intracytoplasmic lipid droplets have been identified in a variety of cancers with expression of ADRP and TIP47 noted in cancer cells 10. The current study expands the role of these lipid droplet associated proteins to non-adipocyte stromal cells in the pancreas and suggests that these cells may have a crucial role in supporting the metabolism of cancer cells by protecting a renewable source for energy to stimulate tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid droplets are composed of a triglyceride-rich core surrounded by a phospholipid monolayer coated by lipid droplet-associated proteins, also known as PAT proteins, which include perilipin 1, adipose differentiation-related protein (ADRP) and tail-interacting protein 47 (TIP47) 7 8. Whereas expression of perilipin is largely confined to adipocytes and steroidogenic tissues,9 expression of ADRP and TIP47 is ubiquitous 10. PAT proteins positively regulate adipogenesis by limiting the access of lipolytic enzymes, including adipose triglyceride lipase (ATGL) and hormone sensitive lipase, to their substrates in the lipid droplet core 7…”
Section: Introductionmentioning
confidence: 99%
“…Notably, normal patient-matched cells were unable to undergo adipogenic differentiation when grown using identical adipogenic conditions [62]. This lipogenic molecular signature is consistent with the ‘clear cell’ ccRCC morphology characterized by cytoplasmic lipid accumulation [78], indicating an important role of neosteatogenesis in ccRCC biology [77]. …”
Section: Integrative Meta-analysis Of Proteomic and Gene-expression Datamentioning
confidence: 71%
“…Consistent with this concept, the accumulation of lipid droplets characteristic of ccRCC cells suggests an activation of the lipogenic pathway and its prominent role in ccRCC biology. Indeed, altered gene expression of fatty acid-binding proteins (FABPs) and adipose differentiation-related protein/adipophilin ( ADFP/PLIN2 ) were consistent with the adipogenic transdifferentiation that is taking place in ccRCC [77]. Specifically, downregulation of FABP1 and FABP3 along with upregulation of FABP5, FABP7 and PLIN2 were revealed at the gene level [62].…”
Section: Integrative Meta-analysis Of Proteomic and Gene-expression Datamentioning
confidence: 99%
“…16 The PAT proteins also have altered expression in different tumor types, including HCC. 17 Genetic variation of the PAT proteins has been linked with type 2 diabetes and obesity, 18 and may inhibit the ability of the lipid droplet to be autophagocytosed and/or transported within the cell, setting off subsequent mechanisms of rancidification of the droplet, cell death, and increased inflammation. 19 A recent study has also shown that alteration of intracellular lipid droplet metabolism through the GTPase, Rab7, may impact lipid droplet breakdown, a mechanism that has similar implications in the pathogenesis of fatty liver disease as well as hepatocarcinogenesis.…”
mentioning
confidence: 99%